2010
DOI: 10.1111/j.1462-5822.2010.01522.x
|View full text |Cite
|
Sign up to set email alerts
|

Haemolysin II is a Bacillus cereus virulence factor that induces apoptosis of macrophages

Abstract: SummaryBacillus cereus is a Gram-positive spore-forming bacterium causing food poisoning and serious opportunistic infections. These infections are characterized by bacterial accumulation despite the recruitment of phagocytic cells. The precise mechanisms and the bacterial factors allowing B. cereus to circumvent host immune responses remain to be elucidated. We have previously shown that B. cereus induces macrophage cell death by an unknown mechanism. Here we identified the toxic component from the B. cereus … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
74
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 85 publications
(75 citation statements)
references
References 62 publications
1
74
0
Order By: Relevance
“…However, PlcR was shown to have no effect on HlyII production (17), suggesting the existence of alternative regulatory pathways. Moreover, disruption of the plcR gene does not lead to eradication of B. cereus pathogenicity in a macrophage-based assay, provided that the hlyII and inhA1 protease genes are intact (40). This observation highlights the important role of hemolysin II in pathogenesis and suggests that the action of HlyII occurs in a regulated, concerted manner.…”
mentioning
confidence: 68%
See 2 more Smart Citations
“…However, PlcR was shown to have no effect on HlyII production (17), suggesting the existence of alternative regulatory pathways. Moreover, disruption of the plcR gene does not lead to eradication of B. cereus pathogenicity in a macrophage-based assay, provided that the hlyII and inhA1 protease genes are intact (40). This observation highlights the important role of hemolysin II in pathogenesis and suggests that the action of HlyII occurs in a regulated, concerted manner.…”
mentioning
confidence: 68%
“…In concert with these in vitro data, we showed that expression of HlyII in B. subtilis renders this organism virulent for the crustacean Daphnia magna (36) and leads to membrane damage in the alga Chara corallina (25); the role of HlyII in the virulence of B. thuringiensis in mice and insects was demonstrated by others (40). The toxic properties of HlyII rely on its ability to disrupt cellular and artificial membranes by pore formation (3).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…All the strains of the B. cereus sensu lato complex seem to carry genes encoding at least one of the known diarrheal toxins (2,11,24), and the expression of these genes is under the control of the PlcR transcriptional regulator, which is activated at the onset of the stationary phase of growth (1). Moreover, the strains of the B. cereus group are also known to synthesize several types of phospholipase C and various hemolysins, collagenases, and proteases (52), which may be implicated in B. cereus pathogenesis (13,42,44,52,57,58). These extracellular membrane-active and tissue-degrading proteins constitute a significant proportion of the proteins secreted by B. cereus strains at the start of the stationary growth phase (20).…”
mentioning
confidence: 99%
“…Although the diarrheal toxin production seems on average higher in strains involved in diarrhea (7), highly toxic strains do not express these toxins (6,7), and other factors are involved during the infection process. For example, HlyII, which causes macrophage death (8), is found in pathogenic strains, although its prevalence in such strains is only about 30% (9). Thus, although these markers provide indications as to the pathogenic potential of a given strain, they do not yet explain the pathogenicity of all strains and are not sufficient to differentiate them.…”
mentioning
confidence: 99%